Factors Influencing the Choice of Delivery Method among Pregnant Women Referring to Comprehensive Health Centers Affiliated with Saveh University of Medical Sciences: Employing the Health Belief Model - Mahmood karimy; Zahra Arab; Parisa Hosseini Koukamari (Mazandaran University of Medical Sciences, 2023)
Introduction and purpose: The caesarean method is used in Iran more than the standard rate recommended by the World Health Organization. Reducing the number of caesarean births and promoting natural births at all levels of the country's health system is a concern of the country's health policymakers. Therefore, the present research aimed to identify the effective factors in selecting the type of delivery based on the Health Belief Model. Methods: This analytical cross-sectional study was conducted among 144 pregnant mothers in the comprehensive health centers of Saveh, Iran. A designed questionnaire based on the constructs of the Health Belief Model (Perceived susceptibility, Perceived severity, Perceived benefits, Perceived barriers, and Self-efficacy) and knowledge was used to determine the beliefs related to the type of the selected delivery. The collected data was analyzed in SPSS software (version 16). Results: Out of 144 individuals, who participated in the study, 52.08% of mothers selected the natural method, and 47.91% chose cesarean as the preferred method of delivery. The structure of perceived barriers, with a mean of 56.50 had the highest mean in the cesarean delivery group. Based on the logistic regression, all six constructs of the Health Belief Model had an impact on predicting the type of delivery, and overall, the model, by 71%, could predict the pregnant mothers' preferred delivery type. Conclusion: Health professionals can reduce the number of unnecessary cesarean births by designing and implementing educational interventions aimed at raising the level of awareness of pregnant mothers and focusing on psychological structures that are effective in behavior, including strengthening self-efficacy in women and removing obstacles regarding natural childbirth.